Penerapan Model Pembelajaran Kooperatif Tipe STAD untuk Meningkatkan Hasil Belajar Siswa pada Penentuan Sifat Larutan Asam – Basa dan Derajat Keasaman (Ph) Larutan di Kelas XI IPA SMAN 2 Tanjung Jabung Timur - Nurasiah Nurasiah (Universitas Jambi, 2016)
The purpose of this study was to improve students' motivation and learning outcomes of students of class XI IPA SMAN 2 Tanjung Jabung Timur. The classroom action research was conducted in the second semester of the academic year 2013-2014 in period of January until March, as much as four times the meetings which were divided into two cycles. Each cycle was performed twice meetings and one evaluation. The subjects of the study were the students of class XI IPA 1. To measure students' motivation and learning outcome used student’s activity data during the learning process with guidance observation data, questionnaire data and achievement test data. Then these data were analysed using descriptive analysis method. In the first cycle shows the percentage of student activities, at the first meeting and the second meeting of 45, 71% and 74, 28%. While in the second cycle, the first meeting and the second meeting of 88, 57% and 94, 28%. The Increasing of learning outcomes in the first cycle was shown learning mastery of 59, 38% with an average value of 70, 17. Whereas in second cycle was shown learning mastery of 87,50% with an average value of 82,76. In addition, the student’s responses are positive towards learning process by implementation of cooperative learning (model STAD) in determination of acid-base solution properties and acidity of solution using natural indicators. It is based on student questionnaire answers which feel happy or satisfied (agree) was 86, 89%. Keywords: Learning outcomes, Learning activities, STAD model, Natural indicators, Learning mastery